On the Optimal Shock Isolation of a System with One and a Half Degrees of Freedom. (1999) - Balandin, D.V.; Bolotnik, N.N.; Pilkey, W.D.
Abstract : The limiting performance of shock isolation of a system with one and a half degrees of freedom is studied. The possibility of using a single-degree-of-freedom model for this analysis is investigated. The error of such an approximation is estimated. Numerical examples are presented.